2022
DOI: 10.3389/fnut.2022.842686
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ε-Polylysine Affects on Gut Microbiota and Plasma Metabolites Profiling in Mice

Abstract: Given the antibacterial effects of ε-polylysine acting on cell membranes, and that glycerol phospholipids are important components of the cell membrane, we hypothesized that ε-polylysine may regulate glycerophospholipid metabolism by modifying the gut microbiota. To test this hypothesis, we treated post-weaning C57 mice with different levels of ε-polylysine (0, 300, 600, and 1,200 ppm) in their basic diet. The growth performance and morphology of intestine were then determined. Modification of the gut microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…[107] Importantly, GRN increased the abundance of Lachnoclostridium, Ruminococcaceae, Enterorhadus, and Mucispirillum that are associated with metabolic protective effects but negatively correlated with glycerolipid and glycerophospholipid metabolites such as LPC and certain ceramides that are associated with obesity and inflammation. [108][109][110] Further correlation analyses demonstrated that GRN-induced microbial and metabolite changes were positively associated with reduced body weight and body fat accumulation as well as improved glucose metabolism. Therefore, the interplay between the gut microbial composition and metabolomics profiles caused by GRN supplementation may provide a potential mechanistic insight for GRN-induced obesity prevention.…”
Section: Discussionmentioning
confidence: 99%
“…[107] Importantly, GRN increased the abundance of Lachnoclostridium, Ruminococcaceae, Enterorhadus, and Mucispirillum that are associated with metabolic protective effects but negatively correlated with glycerolipid and glycerophospholipid metabolites such as LPC and certain ceramides that are associated with obesity and inflammation. [108][109][110] Further correlation analyses demonstrated that GRN-induced microbial and metabolite changes were positively associated with reduced body weight and body fat accumulation as well as improved glucose metabolism. Therefore, the interplay between the gut microbial composition and metabolomics profiles caused by GRN supplementation may provide a potential mechanistic insight for GRN-induced obesity prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Our research also identified a novel association between Bifidobacterium and elevated levels of LysoPI, a lysophosphatidylinositol potentially implicated in immune and inflammatory responses, as suggested by its links to conditions like asthma, COVID-19, and cervical inflammation in existing literature ( Zhang et al., 2018 ; Gu et al., 2022 ; Tu et al., 2024 ). Furthermore, the relevance of phospholipid metabolism, particularly LysoPI, in PPD pathophysiology, underscores the potential of dietary interventions, such as ϵ-polylysine supplementation, to influence gut microbiota and blood metabolite profiles, offering promising avenues for PPD prevention and treatment ( Zhang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipids are key components of all cellular and subcellular membranes and essential for membrane function and integrity. 153,154 Moreover, phospholipids, as conduction signaling of intestinal inflammatory factors, participate in the maintenance of metabolic and immune homeostasis and the inhibition of the inflammatory response, 155 and the pathogenesis of type 2 diabetes, 156 fatty liver disease and schizophrenia-related behaviors. 157,158 Phospholipids are divided into phosphoglycerides and sphingomyelin (SM).…”
Section: Dietary Lipids and Intestinal Homeostasismentioning
confidence: 99%